Extracellular HSPs: The Complicated Roles of Extracellular HSPs in Immunity - Calderwood, Stuart K.; Gong, Jianlin; Murshid, Ayesha (Frontiers in Immunology, 2016)
Extracellular heat shock proteins (HSPs) interact with the immune system in a very complex manner. Many such HSPs exert powerful effects on the immune response, playing both stimulatory and regulatory roles. However, the influence of the HSPs on immunity appears to be black or white in nature - rarely neutral. Thus the HSPs can act as dominant antigens and can comprise key components of anti-tumor vaccines. They can also function as powerful immunoregulatory agents and, as such are employed to treat inflammatory diseases or to extend the lifespan of tissue transplants. Small modifications in the cellular milieu have been shown to flip the allegiances of HSPs from immunoregulatory agents towards a potent inflammatory alignment. These mutable properties of HSPs may be related to the ability of these proteins to interact with multiple receptors often with mutually confounding properties in immune cells. Therefore, understanding the complex immune properties of HSPs may help us to harness their potential in treatment of a range of conditions.